2020
DOI: 10.1177/0956797620960389
|View full text |Cite
|
Sign up to set email alerts
|

Theory-of-Mind Development in Young Deaf Children With Early Hearing Provisions

Abstract: Deaf and hard-of-hearing (DHH) children born to hearing parents have profound theory-of-mind (ToM) delays, yet little is known about how providing hearing assistance early in life, through cochlear implants and hearing aids, influences their ToM development. We thus addressed (a) whether young DHH children with early hearing provision developed ToM differently than older children did in previous research and (b) what ToM understandings characterize this understudied population. Findings from 84 three- to six-y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 37 publications
1
19
0
2
Order By: Relevance
“…This study demonstrates that earlier implantation might foster social development in children who are DHH by providing (via auditory stimulation) the opportunity to experience more verbal interactions with their hearing caregivers. This is in line with the novel longitudinal study of Yu and collaborators ( Yu et al., 2021 ), which showed that children who are DoH with more advanced language abilities had better ToM growth. It is an important study on ToM development in DHH because, in contrast to previous studies, the authors examined a sizable sample ( n = 84) of young DoH children (ages 3–6) with relatively early use of CIs or hearing aids (mean age at provision of hearing aids or cochlear implants = 1.7 years).…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…This study demonstrates that earlier implantation might foster social development in children who are DHH by providing (via auditory stimulation) the opportunity to experience more verbal interactions with their hearing caregivers. This is in line with the novel longitudinal study of Yu and collaborators ( Yu et al., 2021 ), which showed that children who are DoH with more advanced language abilities had better ToM growth. It is an important study on ToM development in DHH because, in contrast to previous studies, the authors examined a sizable sample ( n = 84) of young DoH children (ages 3–6) with relatively early use of CIs or hearing aids (mean age at provision of hearing aids or cochlear implants = 1.7 years).…”
Section: Introductionsupporting
confidence: 87%
“…Moreover, participants varied considerably in terms of communication modality options chosen by families (ranging from exclusively auditory, through bilingual/bicultural to exclusively visual). In a number of studies (see for example, Peterson et al., 2016 ; Yu et al., 2021 ), children with CIs used both spoken language as well as sign language, which makes it possible that their early communication experiences were qualitatively different from those of children who used only one mode of communication.…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of studies demonstrating this relationship (e.g. [14,43,71,73]). For example, Yu et al [71] showed in a longitudinal study that deaf children with CIs who had more advanced language ability had better ToM growth.…”
Section: Tom Development In Deaf Children With Cismentioning
confidence: 95%
“…She found that deaf children with CIs performed worse on the FBT in comparison to preschoolers with typical hearing and suggested that deaf children with CIs could have delayed ToM reasoning. Even though CIs improve development in terms of communication and socialization [66], other researchers have also found that deaf children with CIs exhibit delayed ToM development, in particular false belief understanding, in comparison to their peers with typical hearing [67][68][69][70][71]. For example, Yu et al [71] reported that only 3% of deaf preschoolers with CIs (aged 3-6) succeeded in the false belief task, a dramatically low success rate since the majority of hearing preschoolers pass the false belief task around the age of 5 [6].…”
Section: Tom Development In Deaf Children With Cismentioning
confidence: 99%
See 1 more Smart Citation